BIOFILTRASI N2O DENGAN MEDIUM FILTER BERBASIS KOMPOS: EVALUASI PARAMETER OPERASI - Tania Surya Utami (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2010)
Nitrous oxide (N2O) is a pollutant that has to be reduced because it contributes global warming effect of 310 times higher than CO2. On other hand, agricultural sector contributes over 50% of N2O emissions. The objectives of this research were to study the influence of operating parameters such as flow rate, water content, the addition of natural and synthetic nutrients, and Nitrobacter sp. in biofilter, which used compost medium, to the removal efficiency of N2O. The results showed the best N2O reduction efficiency was 76.9%. This result was obtained at the biofilter with compost medium, which is enriched with synthetic nutrients and inoculated with Nitrobacter sp. This biofilter had a medium height of 50 cm, N2O flowrate of 72 mL/min, and water content of 60%.